2014
DOI: 10.1111/jth.12502
|View full text |Cite
|
Sign up to set email alerts
|

The predictive ability of bleeding risk stratification models in very old patients on vitamin K antagonist treatment for venous thromboembolism: results of the prospective collaborative EPICA study: reply

Abstract: bleeding in elderly patients with venous thromboembolism. J Thromb Haemost 2013; 11: 435-43. 6 Beyth RJ, Quinn LM, Landefeld CS. Prospective evaluation of an index for predicting the risk of major bleeding in outpatients treated with warfarin. Am J Med 1998; 105: 91-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…23,24 Poli et al found a low C-statistic of 0.55 in elderly patients (i.e., age > 80 years) with VKA use. 25 Similar to our work, Kooiman et al recently showed that a HAS-BLED score of !3 is a strong predictor of major bleedings during VKA treatment for acute VTE in the first 6 months, despite a low sensitivity of 54.6%. They recommended that patients should be regarded as high risk by a cutoff of 3 points or higher, leading to a lower specificity (87.3%) on one hand, while avoiding missing a not negligible proportion of major bleeding events on the other.…”
Section: Discussionsupporting
confidence: 89%
“…23,24 Poli et al found a low C-statistic of 0.55 in elderly patients (i.e., age > 80 years) with VKA use. 25 Similar to our work, Kooiman et al recently showed that a HAS-BLED score of !3 is a strong predictor of major bleedings during VKA treatment for acute VTE in the first 6 months, despite a low sensitivity of 54.6%. They recommended that patients should be regarded as high risk by a cutoff of 3 points or higher, leading to a lower specificity (87.3%) on one hand, while avoiding missing a not negligible proportion of major bleeding events on the other.…”
Section: Discussionsupporting
confidence: 89%